2017
DOI: 10.21037/jtd.2017.07.24
|View full text |Cite
|
Sign up to set email alerts
|

Management of pulmonary hypertension from left heart disease in candidates for orthotopic heart transplantation

Abstract: Pulmonary hypertension in left heart disease (PH-LHD) commonly complicates prolonged heart failure (HF). When advanced, the PH becomes fixed or out of proportion and is associated with increased morbidity and mortality in patients undergoing orthotopic heart transplant (OHT). To date, the only recommended treatment of out of proportion PH is the treatment of the underlying HF by reducing the pulmonary capillary wedge pressure (PCWP) with medications and often along with use of mechanical circulatory support. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 68 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…PCWP, mm Hg 18 (12,24) 21 (15,26) 23 (17,28) <.001 15 (9,20) 19 (10,27) 23 ( Continuous data are presented as the median (25th, 75th percentile) and categorical data as number (%).…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…PCWP, mm Hg 18 (12,24) 21 (15,26) 23 (17,28) <.001 15 (9,20) 19 (10,27) 23 ( Continuous data are presented as the median (25th, 75th percentile) and categorical data as number (%).…”
Section: Commentmentioning
confidence: 99%
“…In addition, although in the early 1990s pulmonary dilators, such as sodium nitroprusside, had already been considered to be effective in reducing pretransplant PVR for HTx candidacy, 3 there have been dramatic developments since the 2000s in other pulmonary dilation therapies. [7][8][9] We could speculate that recent post-HTx management with such highly effective dilators might have mitigated a negative impact of PVR on HTx outcomes, especially in the non-LVAD cohort. In the LVAD cohort, however, such dilator therapies might not be as effective as expected because their high PVR values were already fixed, which were not reversible even with LV unloading by LVADs.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Management of PH in AHF remains challenging (259)(260)(261)(262). As combined post-and precapillary PH (CpcPH) may be characterized by superimposed arterial vasoconstriction ± vascular arterial and venous remodelling above and beyond venous congestion, it has been suggested that pulmonary vasodilator therapy utilized for PAH, might be of value in PH due to LHD including LHF.…”
Section: Pre-and Post-operative Management Of Ph Due To Ahfmentioning
confidence: 99%
“…pulmonary vasodilators. 14 The operating theatre teamdincluding the senior surgeon and perfusionistdshould be immediately available when anaesthesia is induced. For patients with an LVAD, a practitioner trained in managing the device should remain in the operating theatre until the device is explanted.…”
Section: Routine Anaesthesia Managementmentioning
confidence: 99%